2009
DOI: 10.1111/j.1744-7976.2009.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Will They Stay or Will They Go? Simulating the Dynamics of Single‐Holder Farms in a Dualistic Farm Structure in Slovakia

Abstract: "This paper investigates the dynamic interplay between farm exit and entry of single-holder farms (SF) in a dualistic farm structure in the Nitra region of the Slovak Republic. Our focus is on economic and noneconomic reasons for farm exit. The impact of varying both the likelihood of succession and the initial farm operator age distributions is studied. An agent-based simulation model of structural change in agriculture is applied, which brings together farm-internal and -external determinants and creates a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…For example, while a major component of some market models such as AgriPoliS (e.g. Happe et al, 2009) and MP-MAS (Schreinemachers and Berger, 2011) is an active land market, while, as we explained above, SimPachamama does not have a land market. Bolivian lowlanders do engage in both off-farm wage labour and in agricultural wage labour, and while there is some degree of both in-and out-migration, the region is still relatively isolated from broader labour markets.…”
Section: Figure 1 Here Figure 2 Herementioning
confidence: 99%
See 1 more Smart Citation
“…For example, while a major component of some market models such as AgriPoliS (e.g. Happe et al, 2009) and MP-MAS (Schreinemachers and Berger, 2011) is an active land market, while, as we explained above, SimPachamama does not have a land market. Bolivian lowlanders do engage in both off-farm wage labour and in agricultural wage labour, and while there is some degree of both in-and out-migration, the region is still relatively isolated from broader labour markets.…”
Section: Figure 1 Here Figure 2 Herementioning
confidence: 99%
“…Specifically, in common with popular complex agricultural simulation models, such as AgriPoliS (e.g. Happe et al, 2009) and MP-MAS (Schreinemachers and Berger, 2011), the simulation comprises distinct 'modules' of submodels that each perform a specific role. First, a farm household module enables agents (households) to make decisions about agricultural land use and labour allocation, and includes separate crop and cattle components.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the design and use of a model based on the diversity of decision-making allows us to connect micro-scale and macro-phenomena by the differentiation of individual and heterogeneous decision-makers as suggested by Matthews et al (2007) and demonstrated in several other studies (e.g. Acosta-Michlik and Espaldon, 2008;Fontaine and Rounsevell, 2009;Happe et al, 2009;Kaufmann et al, 2009). Still, as argued by Verburg (2006), the choice of using models based on either single or multiple algorithms to represent decision-making would depend on the objective of the research itself.…”
Section: Agents' Decision-makingmentioning
confidence: 96%
“…Requirement 1 (microeconomic footing): AgriPoliS (Balmann, 1997;Happe et al, 2009) and MPMAS (Berger, 2001;Schreinemachers and Berger, 2011), as well as the models of Lobianco and Esposti (2010) and Freeman et al (2009) follow the wholefarm planning approach of agricultural economics. They use constrained optimisation based on mathematical programming (MP) techniques to find optimal production and investment plans, while being able to consider a large number of constraints.…”
Section: Specifying the Components Of Mas/luccmentioning
confidence: 99%
“…Requirement 6 (dynamic analysis): The disaggregated and dynamic nature of MAS/ LUCC allows the differentiation of benefits and costs of policy interventions by groups of farmers and the estimation of effects upon the structure of the agricultural sector. For example, Happe et al (2008Happe et al ( , 2009) use their AgriPoliS model to assess the effects of agricultural policies upon structural change in Europe. A similar assessment has been done by Lobianco and Esposti (2010) for an Italian study region.…”
Section: Specifying the Components Of Mas/luccmentioning
confidence: 99%